2016
DOI: 10.1111/pai.12523
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of asthma questionnaire for assessing and achieving best control in preschool‐age children

Abstract: Background: Several patient-/caregiver-completed questionnaires have been utilized for the assessment of asthma control. However, due to the diversity in medical/social circumstances, they may not be optimal for use in all countries. The Japanese pediatric asthma guideline (JPGL) aims at higher levels of control compared with other international guidelines, based on a strong social demand for best care. We developed a new control test to help meet that demand. Methods: A 34-item working questionnaire was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This study emphasizes the need to look at a combination of acute and recurrent asthma symptoms in diagnosis of asthma [9]. A study based on Japanese Pediatric Asthma Guidelines and best asthma control test for preschoolers reported the assessment accuracy as area under the ROC curve of 0.8873 (95% CI 0.8485-0.9199) and 0.8604 (95% CI 0.8049-0.9159) for development and validation datasets, respectively [10]. Another study reported prevalence of asthma as 15.7% by questionnaire and 21.4% by health claims data.…”
Section: Discussionmentioning
confidence: 95%
“…This study emphasizes the need to look at a combination of acute and recurrent asthma symptoms in diagnosis of asthma [9]. A study based on Japanese Pediatric Asthma Guidelines and best asthma control test for preschoolers reported the assessment accuracy as area under the ROC curve of 0.8873 (95% CI 0.8485-0.9199) and 0.8604 (95% CI 0.8049-0.9159) for development and validation datasets, respectively [10]. Another study reported prevalence of asthma as 15.7% by questionnaire and 21.4% by health claims data.…”
Section: Discussionmentioning
confidence: 95%
“…A Japanese pediatric society recently built a new questionnaire, the Best Asthma Control Test for Preschoolers (BEST ACT-P), for children aged < 6 years. They weighed the virtue of Japanese-specific optimization for younger Japanese children 22. However, our study focused more on the universal adaptability that enables us to collaborate internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-administration of questionnaires avoids interviewer bias. 17 , 18 , 26 , 27 On the other hand, the main issue in the validation process of self-administered questionnaires is the capability to understand the items and to appropriately answer them. To facilitate this process, the ChAt questionnaire has been developed with well-defined, objective, and easily understandable questions for parent self-administration.…”
Section: Discussionmentioning
confidence: 99%